Disturbing silence: a look into conflict profile of BTAD/ by urmimala Sengupta - Dutta, Anuradha (New Delhi, 2011)
The book examines the ethnic conflicts of Bodoland Territorial Areas District through the lens of peace research it also highlights the importance of dialogue between the conflicting parties for reviving inter-community relationship in the area. The book provides a rich account of the conflict-induced Internally Displaced Persons IDPS and other stakeholders of the area.
Keywords: Sengupta, Urmimala; Conflict management